Narratives of the Anthropocene: How can the (performing) arts contribute towards the socio-ecological transition?. Issue 1 (1st July 2018) - Ribac, François
In this article, I will examine the possible contribution that the (performing) arts have made to imagine the socio-ecological transition and the Anthropocene era. I will first examine the position occupied by narratives to document and explore these processes and the types of set-ups and approaches that are commonly used in artistic circles. I will then present two projects that were realized in recent years and will examine in particular their relationship with nature and their use of modern technologies. By steering clear of a normative approach, I will finally emphasize the space that these projects leave for their users, their potential dynamics and how they could inspire the performing arts.